Assessment of drug-prescribing perception and practice among dental care providers: a cross-sectional Lebanese study - Aline Hajj; Christel Azzo; Souheil Hallit; Pascale Salameh; Hala Sacre; Frederic Abdou; Nada Naaman; Lydia Khabbaz (Centro de Investigaciones y Publicaciones Farmaceuticas, 2021)
Background: Dentists play an essential role in providing high-quality dental care, taking into consideration the clinical context and concomitant medications taken by the patients. Objective: This study aimed to assess drug-prescribing perception and practices in addition to drug-related educational needs among Lebanese dentists; it also evaluated the need for interprofessional collaboration between dentists and pharmacists. Methods: An exploratory cross-sectional study using an online questionnaire targeted a sample of dentists from all Lebanese districts. Participants gave their consent by accepting to complete the survey (ethics approval reference: USJ-2016-63). The questionnaire consisted of closed-ended questions exploring: 1) drug-prescribing perception, 2) drug-prescribing practice, and 3) collaboration with pharmacists regarding their respective roles in providing appropriate counseling to patients. Two indexes were created: the first evaluated self-confidence in prescribing medications, and the second assessed dentists' confidence in pharmacists. Logistic regressions were performed, taking each index as a dependent variable. Results: A total of 137 dentists completed the survey (59% females; mean age: 42.17; SD: 13.78 years). The majority had a fair to good perceived knowledge in pharmacology and therapeutics (80.3%), only 30.7% reported to be sufficiently equipped to prescribe safely. Dentists exhibited particularly low perceived knowledge about prescribing in elderly patients, dosing, medication use in pregnancy, drug interactions, and adverse reactions. Dentists specialized in periodontics had the lowest odds of having self-confidence in prescribing drugs (aOR=0.25; p<0.001). Also, 64.3% declared that they routinely check a reference source before prescribing, and 78% relied on pharmaceutical companies and medical representatives to get information on medications. While 61% declared that pharmacists should provide oral care counseling, only half of them encouraged their patients to talk to their pharmacists about their medications. Only 15% considered that patients are getting enough counseling from the pharmacist, with a global confidence index below the median value, suggesting the need for more collaboration, especially with periodontists who exhibited the lowest confidence in pharmacists (aOR=0.45). Conclusions: Lebanese dentists reported some lack of knowledge and confidence in prescribing practices. Education, training, and close collaboration between pharmacists and dentists are essential to overcome these problems and avoid potential harm to patients.